BRANDING ACTIVITIES OF THE PREMIER LEAGUE CLUBS: Influence on international consumer buying choices - Rysler, Aneta (My University, 2016)
This thesis takes a look at the branding activities of the Premier League clubs with the particular focus on the impact they have on consumer buying choices. It presents the theory of the branding, examining the sports branding by providing the models of branding and Stewart-Smith sport fans models with providing explanations to the practical side of the argument. Also consumer behaviour and buying choice is discussed in the separate chapter and its implications to this study are thoroughly explained. Additionally, Engle, Blackwell and Miniard models is used to explain consumers buying process. Last section discussed in this project is culture and most known theories regarding these concepts, thus there are theories of Hofstede, GLOBE and Holt. Models used by this study are cultural dimensions models and GLOBE cultural cluster model. By discussing theory and examining theoretical models, this study is able to produce framework that connects all of the presented concepts. The theory from these concepts is used to form the basis for the study that uses the mixture of both Qualitative and Quantitative research. This study collects data by convenient sampling, meaning that the information is collected randomly via online surveys; this way this project is able to provide diverse and mostly unbiased opinions from the respondents. The findings of this thesis present that the consumers have choices in regards to the branding activities and they are allowed to have their choices; however the choices provided by selected football brands are badly distributed and are not reaching the consumers. The way in which they are operating are suggesting that the consumers and potential consumers suggest that they have problems with accessing them and need extra research to find anything about the brand products and services. The findings show that despite brands’ overall positive image and popularity in other sectors, it might suffer due to the inability in providing consumers what they want, and reducing consumers’ their buying choices.
Keywords: Branding; Consumer Behaviour; Sports marketing; Culture; Football branding; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|